SCIENTIFIC AND METHODOLOGICAL FEATURES OF PERSONALIZED EDUCATION (American Journal of Pedagogical and Educational Research, 2024)
This article focuses on the personalization of education based on dividing learners by their level of knowledge, specifically into strong, average, and weak learners. Differentiation is associated with considering the complexity and volume of the learning material (tasks of high, medium, and low complexity). Consequently, the concept of situational interest is explored as an increase in learner activity associated with the initial understanding of new material.